Protection and welfare of animals in Spanish law: key points of laws 3 and 7/2023, of March 28th - Requejo Conde, Carmen (2025)
Twenty years after the crime of animal abuse was introduced for the first time in Spain, the organic law 3/2023 carried out a new modification of the Penal code, and that same day, March 28, 2023, Law 7/2023, on the protection of animal rights and welfare, is promulgated. The reform continued in the line of its predecessors (those of 2010, 2015 and 2021), bringing the legal-criminal regulation of animals as sentient beings closer to that of the person, integrating an increasingly larger number of them (vertebrates), making responsible not only to the individual perpetrator but also to the center that housed the animal, if it were the case, incorporating new aggravating circumstances (now a total of ten, including the death of the animal) and new penalties, some such as fines, not so well received by some doctrinal sectors. This article outlines some of the main reforms and offers some suggestions for improvement. It concludes that, despite the increase in prison sentences for the death of an abused animal, there is still no provision for disqualification from living with animals, and there are no regulations governing the permanent removal of abused animals.